Embedded Ethernet System For Real-Time Communication - Thiagarajan, Durgesh (Universiti Sains Malaysia, 2018)
Real-time communication (RTC) indicates the transmission of data or message between two medium that occur with minimum delay or latency. There is two type of real-time communication such as soft RTC and hard RTC. A common Ethernet network functions based on the carrier sense multiple access with collision detection (CSMA/CD) as the media access control (MAC) protocol for data transmission between shared medium. Moreover, a backoff algorithm is the part of MAC protocol which implements for rescheduling the transmission of a packet after a collision occurs. An embedded Ethernet network model is modified with a different number of nodes and backoff algorithms such as Binary Exponential Backoff (BEB), Modified Binary Exponential Backoff (MBEB), Exponential Increase and Exponential Decrease Backoff (EIED) and Linear/Multiplicative Increase Linear Decrease Backoff (LMILD). The Ethernet network model is used to analyze the performance of the backoff algorithm in a different number of nodes. The end delay of each packet, the number of packet collision and number of packet delivered are determined based on the analysis. MATLAB, Simulink, and Stateflow are used for the Ethernet network model simulation. Based on the simulation, EIED backoff algorithm gave better performance in term of average delay compare to other algorithms. In this case, EIED shows 0.0006257s average delay in 5 nodes, 0.0006252s average delay in 10 nodes and 0.0006260s average delay in 20 nodes.